A Comprehensive Study on the Dynamic Change of Thermal Behavior During Lignocellulose Pyrolysis Catalyzed by Plant-Rich Metallic Elements - Huang, Jiawei; Zheng, Biao; Hong, Zhou; Ouyang, Peiyao; Li, Yuanhua; Wu, Aimin; Li, Huiling (Frontiers in Plant Science, 2021)
Evaluating the pyrolysis of lignocellulose via theoretical and computational approaches is of great importance for the efficient utilization of biomass. In this work, the dynamic changes in physicochemical properties of eucalyptus and bamboo during plant-rich metallic elements catalyzed pyrolysis process were investigated, and their thermal decomposition behavior were explored by kinetic analysis. Results showed that the metal absorption capacity and thermal stability of eucalyptus were better than those of bamboo. The temperatures corresponding to the initial devolatilization and highest weight loss value of eucalyptus/bamboo decreased in the catalysis order of Mg > Fe > Ca > Cu > K > Na. FT-IR results showed that the thermal stability of ester bond of glucuronoarabinoxylan was higher than that of acetyl groups. The maximum weight loss rate could be observed for samples with the lowest metal-loaded concentration (5%). Moreover, Mg and Fe presented the better catalytic performance for facilitating the lignocellulose pyrolysis in comparison with other investigated metallic elements.